Financial stress among female entrepreneurs in Nigeria: The buffering effect of financial literacy - Christopher Chinedu Onochie; Gilbert Ogechukwu Nworie (Goodwood Publishing, 2025)
Purpose: As financial stress considerably hinders the success and sustainability of female entrepreneurs in Nigeria, this is exacerbated by financial illiteracy, which leaves many unable to manage their business finances effectively. In view of the above problem, this study examines how financial literacy affects financial stress among female entrepreneurs in Nigeria. Methods: This study used a descriptive survey research design. The sample consisted of 285 female entrepreneurs selected from a population of 994 female entrepreneurs in Ebonyi State. Primary data were collected using a structured questionnaire. Ordinal regression analysis was conducted to test the hypotheses. Results: The use of financial products and services significantly reduces financial stress (?1 = -0.413391; p-value = 0.0261), budgeting significantly reduces financial stress (?2 = -0.080064; p-value = 0.0364), and emergency fund creation significantly reduces financial stress (?3 = -0.226254; p-value = 0.0094). Conclusion: Financial literacy mitigates the challenges of financial stress by empowering women with the knowledge and skills required to make informed financial decisions. Limitations: The study was limited to female entrepreneurs in Ebonyi State, which may not be representative of other regions or genders. Contributions: This study is useful in the fields of entrepreneurship, finance, and gender studies, particularly for policymakers, financial educators, and organizations that support female entrepreneurs. Recommendation: The Nigerian Ministry of Commerce, Industry, and Business Development should initiate entrepreneurial financial literacy programs incorporating practical tools, such aThe s interactive workshops on budget management, digital budgeting applications, and real-life case studies, to enhance budgeting skills among female entrepreneurs.